Clinical Predictive Factors of Response to Biologics in IBD - Roxana SADAGURSCHI; A. DOBROMIRESCU; Ruxandra BABIUC; Lucian NEGREANU (Modern Medicine)
Background: Growing insights into complex molecular pathways involved in the pathogenesis of inflammatory bowel diseases (IBD) have led to advent of new treatment options. Currently, there are three classes of biological agents approved for the treatment of IBD: anti-tumor necrosis factor agents (anti-TNFs), vedolizumab (VDZ) and ustekinumab. Each of these molecules have different targets in the inflammatory process, inhibiting specific mediators. Since the therapeutic options tend to increase and become more and more variate, it would be important to establish predictive markers of response to choose the best therapeutic option for the most suitable patient. Nowadays, the concept of „personalized medicine” which means selecting the right drug for the right person at the right time based on the characterization of an individual’s phenotype and genotype seems to be more reasonable and tends to replace the strategy “one drug suits all” that we used for many years. Aim: To present the currently available data regarding the clinical predictors of response not only to anti-TNFs, but also to VDZ and ustekinumab. Methods: A literature search was performed in PubMed to identify publications reporting on predictive factors of response to biologic therapy in patients with IBD, using pre-defined keywords. We selected RCTs, observational studies, reviews and meta-analyses. Results: For anti-TNF agents most of the evaluated factors have not proved to be accurate enough as to enter daily clinical practice as a decisive tool to enable an individualized therapeutic approach. Factors identified as potential predictors include disease behavior/ phenotype, disease severity, CRP, prior anti-TNF exposure, but the results were variable and sometimes conflicting. For VDZ, even more discouraging results were obtained, with only few factors (disease severity and prior anti-TNF exposure) showing limited value. Regarding ustekinumab, no predicting factor has been reported yet to be helpful in clinical practice. Conclusion: Current scientific results cannot establish a single biomarker that fulfills all criteria for being an appropriate prognostic indicator for response to any biological treatment in IBD. Further research is needed to identify new and more reliable predictors or to better evaluate the existing ones.